PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN SALES AND MARKETING DI HOTEL THE RITZ CARLTON JAKARTA PACIFIC PLACE - Fauzan Ihza; Feri Ferdian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research was conducted by the authors because there were several employee engagement problems that were felt by sales & marketing employees at work. This is what the writer found while carrying out a certified internship at The Ritz Carlton Jakarta Pacific Place. The purpose of conducting this research is to find out how much influence employee involvement and employee performance have at The Ritz Carlton Jakarta Pacific Place. The type of research that the authors conducted was quantitative using a causal associative approach, this aims to influence employee engagement (X) on the performance of employees (Y) who work at The Ritz Carlton Jakarta Pacific Place. The population of the research that the authors conducted were all sales & marketing employees who worked at The Ritz Carlton Jakarta Pacific Place. The sample in this study amounted to 34 respondents, using a saturated sampling technique. Collection was carried out primary and secondary by distributing questionnaires and obtained directly from the relevant hotel management. In testing the hypothesis using a simple linear regression test, data processing where used SPSS version 25.00. The results of the research that the authors conducted were: 1) employee engagement was in the good category (81.23%), (2) employee performance was in the very good category (91.94%). There is an influence between the X and Y variables with the acquisition of an R square of 0.173, which means that the influence between the X variable or employee engagement on the Y variable or employee performance is 17.3%. Test the simple linear regression hypothesis with a calculated F value of 2.525 with a significance of 0.002 <0.05, where the employee engagement variable has a significant effect on employee performance variables.Key word: Employee engagement, Employee performance, Sales & marketing.